Diseño e implementación de un sistema EVA como apoyo al Desarrollo de Habilidades del Pensamiento de los estudiantes de Tercer Año de Bachillerato General Unificado de la Unidad Educativa “Juan de Velasco” del Canto Riobamba Provincia de Chimborazo, Periodo Lectivo 2015 - 2016 - Paguay Cujilema, Jenny Verónica (2016)
The research work had as objective: to design and to implement a Virtual Learning Environment, aimed at students of the third year of General Unified High School of the Educational Unit "Juan de Velasco" to develop the Thinking Skills in the academic year 2015 - 2016. The research is applied, technological, in this it was used the PACIE methodology for the implementation of the environment that was used in the developing of the Thinking Skills. The sample consisted of students from the Third Year of the General Unified School of the Educational Unit "Juan de Velasco". For the data collection, it was applied a survey aimed to the students in order to measure the availability to use the environment, resulting in nearly all students consider the virtual learning environment (EVA) serves as the support for the development of the Thinking Skills. The EVA was developed in the LMS Moodle which allowed evidence that the main advantage is that it allows us to implement the questionnaires are the main activity with which work was done, and is also a friendly virtual classroom environment with the user. Finally, we reached the following conclusion the data was collected, acquired and digitized the questions in the Exam View tool on Thinking Skills in areas Reasoning Numerical Verbal and Abstract to implement databases of questionnaires to be used in the Virtual Learning Environment.